2013
DOI: 10.1002/glia.22449
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D3 receptor activation promotes neural stem/progenitor cell proliferation through AKT and ERK1/2 pathways and expands type‐B and ‐C cells in adult subventricular zone

Abstract: The neurotransmitter dopamine acts on the subventricular zone (SVZ) to regulate both prenatal and postnatal neurogenesis, in particular through D(3) receptor (D(3) R) subtype. In this study, we explored the cellular mechanism(s) underlying D(3) R-mediated cell proliferation and tested if systemic delivery of a D(3) R agonist would induce SVZ multipotent neural stem/precursor cell (NSC/NPC) proliferation in vivo. We found that treatment with the D(3) R agonist, 7-OH-DPAT, enhances cell proliferation in a dose-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…In contrast, the activation of either Akt or ERK1/2 has been shown to promote proliferation in adult hippocampal (Peltier et al, 2007; Ma et al, 2009) and in adult subventricular zone (Torroglosa et al, 2007; Lao et al, 2013) neural stem cell cultures. Similarly, in adult spinal cord NSPC cultures, we have shown that the inhibition of either the PI3K/Akt pathway or the MEK/ERK1/2 pathway, but not the PLCγ pathway, markedly reduced cell division (proliferation).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the activation of either Akt or ERK1/2 has been shown to promote proliferation in adult hippocampal (Peltier et al, 2007; Ma et al, 2009) and in adult subventricular zone (Torroglosa et al, 2007; Lao et al, 2013) neural stem cell cultures. Similarly, in adult spinal cord NSPC cultures, we have shown that the inhibition of either the PI3K/Akt pathway or the MEK/ERK1/2 pathway, but not the PLCγ pathway, markedly reduced cell division (proliferation).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the close proximity of the subventricular zone with the striatum makes it a potential source of endogenous neurons that could be engaged in brain repair strategies for this neurodegenerative disease. The dense DA innervation of the subventricular zone observed in HD brains indicates that this monoamine, known to exert a robust excitatory influence upon adult neurogenesis (Baker et al, 2004; Hoglinger et al, 2004; Van Kampen et al, 2004; Lao et al, 2013), might significantly contribute to cell proliferation in HD and could have a crucial role in intrinsic mechanisms involved in attempts to produce new neurons in order to compensate for the massive striatal neuronal losses that occur. It could also play a role in striatal gliogenesis that takes place in such a pathological condition (Sapp et al, 2001).…”
Section: Striatal Da Innervation In the Hd Postmortem Brainmentioning
confidence: 99%
“…Our study suggests a potential involvement of AT 2 in each of these stages. The proliferative, survival, and prodifferentiation effects of CGP42112A may be attributed, at least in part, to the observed early elevation of the neurotrophins (e.g., BDNF and NGF) and their downstream effectors ERK1/2 and Akt [29,70,[81][82][83]. Of note, as BrdU injections were given at early time points after TBI, when apoptotic events still take place [42], we cannot entirely exclude the possibility of false-positive labeling of neurons undergoing apoptosis.…”
Section: Cgp42112a Treatment Post-tbi Induces Neurogenesismentioning
confidence: 99%